Relationship between temperamental dimensions and infant limb movement complexity and dynamic stability - Arellano-Véliz, Nicol A.; Laudańska, Zuzanna; Duda-Goławska, Joanna; Cox, Ralf F. A.; Tomalski, Przemysław (Infant behavior and development, 2025)
Infant temperament reflects behavioral responses to stimulation, while the motor system undergoes significant developmental changes throughout infancy, influenced in part by caregivers’ mental well-being. This study examines the associations between temperament and motor system organization across three distinct social interaction tasks at 6 and 12 months of age. To account for the role of the caregiver’s mental well-being, we also included maternal trait anxiety in our analysis. A longitudinal sample of 83 infants at 6 months and 59 infants at 12 months participated in three caregiver-infant tasks: book-sharing, playing with manipulative toys, and rattle-shaking. Infant limb movements were recorded using wearable accelerometers, and we applied Multidimensional Recurrence Quantification Analysis (MdRQA) to extract Entropy (reflecting motor system complexity) and Mean Line (reflecting motor system stability). Using mixed-effects models, we examined the predictive effects of task and temperament variables: Negative Affectivity (NEG), Positive Affectivity or Surgency (PAS), and Orienting and Regulatory Capacity (ORC). Our results suggest that Negative Affectivity measured at 6 months predicted increased motor system Entropy and Mean Line concurrently at 6 months as well as longitudinally at 12 months. Temperamental variables measured at 12 months of age did not predict infants’ motor systems’ complexity and stability at the same time point. At 12 months, task conditions modulated both Entropy and Mean Line, suggesting greater sensitivity to contextual differences later in infancy. Additionally, higher maternal trait anxiety (measured at 4 months) predicted decreased motor system Entropy and Mean Line at 12 months. Our results have implications for understanding the early developmental pathways of motor system organization, its relationship with temperament, and the influence of caregiver mental well-being on infant motor development.
Online verfügbar: 12. März 2025
Gesehen am 13.08.2025